2021
DOI: 10.3390/polym13183104
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Methylene Blue Removal by Nano TiO2 Using Deep Neural Network

Abstract: This paper deals with the prediction of methylene blue (MB) dye removal under the influence of titanium dioxide nanoparticles (TiO2 NPs) through deep neural network (DNN). In the first step, TiO2 NPs were prepared and their morphological properties were analysed by scanning electron microscopy. Later, the influence of as synthesized TiO2 NPs was tested against MB dye removal and in the final step, DNN was used for the prediction. DNN is an efficient machine learning tools and widely used model for the predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Recently, ANN has shown its effectiveness in the prediction of not only tensile strength but many other parameters including dye removal efficiency and functional properties of composites [ 25 , 26 , 27 , 28 ]. ANN has the advantages of high nonlinearity resolution, self-learning and mapping capability between input and output variables without introducing a mathematical model between nonlinear data.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ANN has shown its effectiveness in the prediction of not only tensile strength but many other parameters including dye removal efficiency and functional properties of composites [ 25 , 26 , 27 , 28 ]. ANN has the advantages of high nonlinearity resolution, self-learning and mapping capability between input and output variables without introducing a mathematical model between nonlinear data.…”
Section: Introductionmentioning
confidence: 99%
“…For a variety of thermal insulation-related applications, including vacuum insulation, cryogenic insulation, and building insulation, flexible aerogels are promising materials . These materials can be used for a variety of industrial and energy-related applications due to their high flexibility, transparency, low thermal conductivity, high surface area, and sharp pore size distribution. , Aerogels are a good option for addressing serious environmental issues due to their low density and biodegradability . Recently, Han et al utilized both freeze-casting and the thermal reduction method to produce polymeric flexible aerogels, where TiO 2 and chitosan were used as thermal insulating materials.…”
Section: Applications Of Flexible Aeroglesmentioning
confidence: 99%
“… 91 , 92 Aerogels are a good option for addressing serious environmental issues due to their low density and biodegradability. 93 Recently, Han et al utilized both freeze-casting and the thermal reduction method to produce polymeric flexible aerogels, where TiO 2 and chitosan were used as thermal insulating materials. The fabricated aerogels showed high-temperature service performance, good thermal insulation, and excellent mechanical properties.…”
Section: Applications Of Flexible Aeroglesmentioning
confidence: 99%
“…Aerogels have the advantages of biodegradability and low density that make them a good choice for solving serious environmental problems. Researchers have proposed and developed many techniques that produce green and sustainable electrodes, based on aerogels, as a solution for pollution and other environmental concerns [ 73 , 74 , 75 ]. In an experimental study, Strobach et al reported the synthesis of optically transparent and thermally insulating monolithic silica aerogels with high solar transparency, especially developed for the solar thermal receiver.…”
Section: Applications Of Aerogelsmentioning
confidence: 99%